2014
DOI: 10.18632/oncotarget.1914
|View full text |Cite
|
Sign up to set email alerts
|

HMGA1 silencing restores normal stem cell characteristics in colon cancer stem cells by increasing p53 levels

Abstract: ABSTRACT:High-mobility group A1 (HMGA1) proteins are architectural chromatinic proteins, abundantly expressed during embryogenesis and in most cancer tissues, but expressed at low levels or absent in normal adult tissues. Several studies have demonstrated that HMGA1 proteins play a causal role in neoplastic cell transformation. The aim of this study was to investigate the role of these proteins in the control of cancer stem cells (CSCs), which have emerged as a preferred target in cancer therapy, because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 34 publications
2
60
0
Order By: Relevance
“…For overexpression, the pCDNA3.1-HMGA1 and the empty control vectors were constructed as previously described [10]. For down-regulation, the hairpin RNA interference plasmid for human HMGA1 (pLKO.1-HMGA1, TRCN0000018949) and the scramble control pLKO.1-Puro plasmid (SHC002) were purchased from Sigma-Aldrich (Sigma-Aldrich, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For overexpression, the pCDNA3.1-HMGA1 and the empty control vectors were constructed as previously described [10]. For down-regulation, the hairpin RNA interference plasmid for human HMGA1 (pLKO.1-HMGA1, TRCN0000018949) and the scramble control pLKO.1-Puro plasmid (SHC002) were purchased from Sigma-Aldrich (Sigma-Aldrich, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…Of its many roles, HMGA1 negatively regulates TP53 [10] and promotes an undifferentiated pluripotent stem-like cell state through the induction of SOX2 , LIN28 and cMYC [11]. HMGA1 also directly activates genes involved in tumor growth, migration, invasion, resistance to drug-induced cell death and epithelial-mesenchymal transition in cancer cells [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have indicated that p53 may be involved in the regulation of colon cancer stem cells (33,34), the precise mechanisms are relatively unclear. The present study demonstrated that wild-type p53 transactivated the promoter of the CD133 gene, indicating that the CD133 gene may be a novel target of p53 in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Their overexpression is associated with a highly malignant phenotype and correlates with the presence of metastasis and reduced survival [8, 9]. Several studies implicate the expression of the HMGA genes in the process of carcinogenesis [10-18]. However, although HMGA overexpression is known to play a critical role in malignant cell transformation, the mechanisms regulating HMGA protein levels remain largely obscure.…”
Section: Introductionmentioning
confidence: 99%